Pengaruh Pengetahuan terhadap Pemakaian Metode Kontrasepsi Jangka Panjang di Wilayah Kerja Puskesmas Botania Tahun 2023 - Ridni Husnah; Rici Gusti Maulani; Purwanti Purwanti (Universitas Pahlawan Tuanku Tambusai, 2023)
Active contraseption users in March 2020 decreased compared to February 2020 throughout Indonesia. IUD birth control in February 2020 from 36,155 dropped to 23,383. The purpose of this study is to determine whether there is an influence of knowledge on the use of long-term contraceptive methods in the Botania Health Center area in 2023. This study used quantitative method with a cross-sectional approach. The population in this study is contraceptive acceptors at the Botania Health Center during February 2023 as many as 208 people. This research used Purposive Sampling (Slovin Technique). The data collection processed by observation and questionnaire distribution. This research statistical test using Chi-square parametric test. The results of the univariate analysis of the majority of respondents' knowledge were sufficient 37 people (54.4%) and the majority of respondents used the MKJP contraceptive method with a total of 37 people (54.4%). The results of the bivariate analysis showed a significant influence between knowledge on the use of long-term contraceptive methods in the Botania Health Center area in 2023. (p.value 0.018). The conclusion of this research there is a significant influence between knowledge on the use of long-term contraceptive methods in the Botania Health Center area in 2023. Researchers hope that health workers can further provide knowledge and introduction to MKJP to couples of childbearing age with a better approach so that they can increase the use of MKJP even better in the futur